Histopathological and Digital Morphometrical Evaluation of Uterine Leiomyoma in Brazilian Women - Ana Paula Fernandes da Silva; Luciano de Albuquerque Mello; Erlene Roberta Ribeiro dos Santos; Silvania Tavares Paz; Carmelita Lima Bezerra Cavalcanti; Mario Ribeiro de Melo-Junior (Hindawi Limited, 2016)
The current study aims to evaluate histopathological and digital morphometrical aspects associated with uterine leiomyomas in one hundred and fifty (150) patients diagnosed with leiomyoma. Uterine tissues were subjected to the histopathological and digital morphometric analyses of the interstitial collagen distribution. The analysis of medical records indicates that most of the women diagnosed with uterine leiomyomas (68.7%) are between 37 and 48 years old. As for the anatomic location of the tumors, approximately 61.4% of the patients had intramural and subserosal lesions. In 50% of the studied cases, the patients developed uterine leiomyomatosis (with more than eight tumors). As for the morphometric study, the average size of the interstitial collagen distribution held approximately 28.53% of the capture area, whereas it was of 7.43% in the normal tissue adjacent to the tumor. Another important aspect observed in the current study was the high rate of young women subjected to total hysterectomy, a fact that resulted in early and definitive sterility.